Irish voices for Irish visions: Gael Linn’s documentary film projects - Heather Macdougall (University of Edinburgh, 2009)
This paper seeks to analyse three important documentary film projects of Gael Linn – the Amharc Éireann newsreel series, Mise Eire and Saoirse? – in terms of the connection that they create between Irish-language cinema and the ideologies of Irish nationalism. Since Gael Linn was founded in 1953 in direct response to a perceived failure on the part of the newly independent Irish state to revive the Irish language, I will begin with a very short overview of the Irish government’s efforts in this direction, followed by an examination of the goals and objectives of Gael Linn when it was founded, before moving on to an analysis of the film projects.